Prevalence of Prohibited Questions During Plastic Surgery Integrated Residency Interviews: Regional Analysis and Contextual Insights - Athena Zhang, MD; Esperanza Mantilla-Rivas, MD; Ashley E. Rogers, MD; Theodore S. Hyman, MD; Md Sohel Rana, MBBS, MPH; Albert K. Oh, MD; Lisa R. David, MD; Jeffrey E. Janis, MD, FACS; Gary F. Rogers, MD, JD, LLM, MBA, MPH (Plastic and Reconstructive Surgery, Global Open)
Background:. This study examined the prevalence of prohibited questions encountered during the 2024 integrated plastic and reconstructive surgery (PRS) residency interview process. Methods:. An anonymous, 13-question minimum Research Electronic Data Capture survey was distributed to 2024 cycle applicants to integrated PRS residency programs in the United States. The survey covered personal characteristics and the frequency, type, context, and source of prohibited questions. Results:. A total of 74 applicants completed the survey, yielding a 23.1% response rate. In all, 52.7% of respondents reported being asked at least 1 prohibited question during the interviews. Of those, 90% of respondents reported answering these questions truthfully, and 43.3% stated that prohibited questions affected their ranking of particular programs. Female applicants were 5.8 times more likely to be asked about program ranking than male applicants (43.2% versus 7.4%, P = 0.001). Non-White applicants (Hispanic/Latino and Asian) were 5.88, 4.13, and 3.08 times more likely to be asked specific prohibited topics such as family planning (P = 0.004), career balance (P = 0.038), and marital status (P = 0.025), respectively, compared with White applicants. Additionally, programs in the US South and Northeast were 1.52 times more likely to ask prohibited questions compared with programs in the West and Midwest combined. Conclusions:. Prohibited questions remain a prevalent issue in integrated PRS residency interviews. Even when not malicious, such questions may introduce potential bias into the process and can be unethical or illegal. Programs and applicants must work to highlight and eliminate these questions from the application process.